Treatment of MCF-7 and MDA-MB-231 human breast cancer cell lines with erythropoietin, doxorubicin and their combination - Radwan, Esam M. (2015)
The cancer chemotherapies are formulated to target the rapidly proliferating cancer cells more efficiently than those normal cells of low proliferating rate. In cancer therapies erythropoietin (EPO) is often used in combination with chemotherapeutic drugs to treat the cancer-associated anemia. In this study, it is hypothesized that EPO does not modify the cytotoxic effect of doxorubicin (DOX). Thus the objective of the study was to determine the effect of DOX-EPO combination treatment on human breast cancer cell lines. The cytotoxicity of DOX (1 μg/mL) alone or in combination with EPO (1 μg/mL DOX – 1 IU/mL EPO) against two human breast cancer cell lines, the MCF-7 and MDA-MB-231 cell, was determined by 3-4,5-dimethylthiazol- 2-yl)-2,5-diphenyl tetrazolium bromide cell viability assay, neutral red uptake and lactate dehydrogenase assays. The activity caspases and morphology of the treated cells were also determined. Doxorubicin inhibited MCF-7 cells with IC50 of 0.217±0.05 and 0.127±0.01 μg/mL when determined by the MTT and NR assay respectively, at 72 hours.On the MDA-MB-231 cells the IC50 of DOX was 0.12±0.09 μg/mL and 0.118±0.04 μg/mL by the MTT and NR assay, respectively, at 72 h of treatment. Doxorubicin in combination with EPO did not exhibit any notable difference in cytotoxicity to the cell lines when a compared to DOX alone. The anti-proliferative effect of DOX alone was obvious on the MCF-7 and MDA-MB-231 cell, showing decline in cell counts from 27.4 and 27.3 × 105 to 2.1 and 7.0 × 105 cells respectively, after 72 h of treatment. Light microscopic examination of DOX-treated MCF-7 and MDA-MB-231 cells at 72 h demonstrated apoptotic changes in cellular morphology characterized by cell rounding followed by a loss of adherence with subsequent cell shrinkage and blebbing. The mechanism of cell death was determined through the caspases-3 and -9 activities of the treated cells. The results demonstrated that caspases-3 and-9 activities were significantly (p<0.05) elevated early in DOX-treated MCF-7 MDA-MB-231 cells after 24 h, suggesting the apoptotic effect of DOX is via the mitochondrial pathway. Erythropoietin did not cause any change in caspase level in the treated cells. This study shows that EPO did not modify the cytotoxic effect of DOX on MCF-7 and MDA-MB-231 cells and thus is safe to be used with DOX in the treatment of breast cancers in patients with concurrent anemia.